A cultural study of the epidemic in the context of racism through the novel « Slave corrals » (مجلة إحالات, 2026)
This intervention directs a cultural perspective towards the colonial crematoriums set up in the nameof eradicating the plague, in which the negro class offered a sacrifice of “superior white” the stamp of decadence and filth and banished far away in isolated squatters, whose borders were defined by theclassification logic of the corral, an indication of racial decadence and lack of humanity that they equatedwith animals. It is an approach to the cultural question about “double oppression”, (the oppression of racism and the oppression of colonialism) imposed on Negroes, which is exacerbated by the epidemic, using post-colonial cultural theories and the related fields of Negroism and “racial discrimination”. Relying on the novel slavepens by the Libyan writer “Najwa Bin Shtwan, which recounted the tragedies of black people under slaveryand colonialism, and was exposed to the plague that swept the country, and the slaves paid its price.